2014
DOI: 10.1111/joid.12031
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Past: What Does history offer the Discipline of Interior Design?

Abstract: IntroductionAt the university where I teach faculty members are often bemused by what might be referred to as a Millennial's approach to design. Our concern typically revolves around student research-particularly the use of design precedent. Almost too tempting to ignore, Pinterest and Google images on the World Wide Web provide the student with ready access to a plethora of ideas and concepts on which to base interior design projects.But how sound is this footing? These pinned and Googled images are more ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Perhaps mentioning them here will lead to more discovery of their histories and contributions. As Kirkham (2002) and other researchers have noted, documenting these individual stories is an important piece of the history of the interior design profession and discipline (Cunningham, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps mentioning them here will lead to more discovery of their histories and contributions. As Kirkham (2002) and other researchers have noted, documenting these individual stories is an important piece of the history of the interior design profession and discipline (Cunningham, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In her perspective for the Journal of Interior Design , Cunningham (2014) discusses the utility of history for the discipline of interior design. She argues that taking a more nuanced approach to the past can underscore the diversity of individual perspectives and experiences of interior design within their historical context.…”
Section: Overview Of the Contextmentioning
confidence: 99%
“…Therefore, interiors can be seen as “the dynamic backdrop for human social activity, embodying human social interaction, perception and personal, social, psychological and cultural dynamics, which are contextualized around the complex yet everyday interface with objects, other people, and the surrounding three‐dimensional enclosure” (Poldma, , p. 31). To emphasize the importance of the contextual responsiveness of interior design, the notion of “interior design in context” has been introduced as essential within the current theoretical underpinnings of the discipline (Cunningham, , p. vii) . Accordingly, the theoretical debate also bears witness to an increasing interest in the societal impact of interiors (Anderson, Honey, & Dudek, ; Antiquino, ; Caan, ; Danko, Meneely, & Portillo, ; Embrechts, Manders, & Somers, ; Gaines & Bourne, ; Guerin & Martin, ; Mendoza, ; Pable, ; Pable & Fishburne, ; Pable & Waxman, ; Poldma, Jutras, Labbé, & Tissaoui, ; Smith, Lommerse, & Metcalfe, ; Vaikla‐Poldma, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional legal history narrative, which tended to isolate law, fell short of her expectations. She found that most historical accounts did not “embed law in social context” and “often treated legal issues and periods of time in isolation” while “non‐legal histories” typically ignored the role of law in shaping the world (Cunningham, , p. vi). Cunningham points out parallels between the legal and the interior design discipline.…”
mentioning
confidence: 99%
“…In order to take up the previously mentioned design challenge, our future society is in need of interior architect students that can sense these societal ambitions and integrate them into the interior design process that generates "fitting" or suitable interior designs (Giunta, 2009;Attiwill, 2011;Caan, 2011;Cunningham, 2014).…”
Section: Introductionmentioning
confidence: 99%